Cepharanthine as an effective small cell lung cancer inhibitor: integrated insights from network pharmacology, RNA sequencing, and experimental validation - Zhao, Fengyun; Ding, Zhaowei; Chen, Mengting; Ji, Mingfang; Li, Fugui (Frontiers in Pharmacology, 2024)
Small cell lung cancer (SCLC) is an aggressive malignancy with limited treatment options and poor prognosis, underscoring the need for new therapeutic agents. In this study, we screened a natural compound library of 640 compounds and identified Cepharanthine (CE) as a promising candidate with significant anti-SCLC activity. In vitro assays demonstrated that CE significantly suppresses SCLC cell proliferation, colony formation, migration, and invasion while inducing apoptosis. In vivo, CE treatment notably reduced tumor volume in xenograft models. To elucidate the molecular mechanisms underlying CE's anti-SCLC effects, we employed network pharmacology and RNA sequencing (RNA-seq) analysis. Network pharmacology identified 60 potential target genes, and enrichment analysis indicated that these genes play a key role in regulating cholesterol metabolism. Interestingly, although cholesterol-related genes were significant in the analysis, they did not rank among the top hub genes predicted by network pharmacology. RNA-seq and experimental validation further revealed that CE inhibits cholesterol synthesis in SCLC cells by downregulating key enzymes (HMGCR, HMGCS1, IDI1, FDFT1, and SQLE). Molecular docking confirmed that CE binds favorably to these enzymes. Furthermore, these enzymes were highly expressed in SCLC cells, with elevated levels of HMGCS1, HMGCR, and IDI1 associated with poor prognosis. Functional experiments demonstrated that silencing these genes significantly inhibits SCLC cell proliferation. This study identifies CE as a potential effective SCLC inhibitor through cholesterol synthesis suppression and uncovers novel therapeutic targets for the disease.